2015
DOI: 10.1371/journal.pone.0137519
|View full text |Cite
|
Sign up to set email alerts
|

RhoA Ambivalently Controls Prominent Myofibroblast Characteritics by Involving Distinct Signaling Routes

Abstract: IntroductionRhoA has been shown to be beneficial in cardiac disease models when overexpressed in cardiomyocytes, whereas its role in cardiac fibroblasts (CF) is still poorly understood. During cardiac remodeling CF undergo a transition towards a myofibroblast phenotype thereby showing an increased proliferation and migration rate. Both processes involve the remodeling of the cytoskeleton. Since RhoA is known to be a major regulator of the cytoskeleton, we analyzed its role in CF and its effect on myofibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…This is in line with the previous observations that RhoA is a key regulator of the mechanical properties of fibroblasts (31)(32)(33). These mechanical changes in the RhoA-KO fibroblasts were linked to the loss of wide stress fibers and large focal adhesions.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the previous observations that RhoA is a key regulator of the mechanical properties of fibroblasts (31)(32)(33). These mechanical changes in the RhoA-KO fibroblasts were linked to the loss of wide stress fibers and large focal adhesions.…”
Section: Discussionsupporting
confidence: 92%
“…This allowed us to compare the effects of Fasudil and H1152P, to demonstrate the concentration-dependent effect of SR-3677, to confirm that ROCKs play a role downstream of TGF-β in cardiac fibroblasts behaviour as suggested before [10], and to validate the importance of ROCKdependent signalling events like the actin-MRTF-LOX regulation. In addition to the presented pharmacological study we have demonstrated in the past that ECT can be prepared from male and female cells to study sex-differences in cardiac fibrosis and from virally transduced cells allowing loss-and gain-of function studies [15,18,30,42].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, ROCKs regulate fibrosis-associated genes, including connective tissue growth factor (CTGF), fibroblast growth factor 2 (FGF2), α-smooth muscle actin (SMA) and pro-collagen I [10,[13][14][15]. ROCKs are also implicated in cardiac fibroblast migration and proliferation [16][17][18]. All in vitro studies have been carried out using purified cardiac fibroblasts in 2D cultures, and the effects of ROCK inhibition on the behaviour of cardiac fibroblasts embedded in a more physiological 3D environment have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary rat tail and cardiac fibroblasts were derived from neonatal rats (day 1–3) and cultivated as described earlier …”
Section: Methodsmentioning
confidence: 99%